SELF-COMPASSION FOR TEENS 129 activities and practices to cultivate kindness;129 activities and practices to cultivate kindness. - GRAY, LEE-ANNE (PESI PUBLISHING & MEDIA, 2016)
Self-compassion is the key for teens to develop empathy and manage self-criticism, while increasing resilience and well-being.